Prolonged Airway Obstruction after Posterior Occipitocervical Fusion: A Case Report and Literature Review - Masahiro Morita; Masuhiro Nobuta; Hirotsune Naruse; Hiroaki Nakamura (Advances in Orthopedics)
The purpose of this paper was to inform the reader that prolonged upper airway obstruction after posterior cervical spine surgery is a possible complication for patients with metastatic tumor of upper cervical spine. A 49-year-old man presented severe neck pain during posture changes due to metastatic spinal tumor of C2. Occipitocervical fusion following removal of the posterior arch of C1 and laminectomy of C2 via the single posterior approach was performed 2 weeks after radiation therapy. After the surgery, life-threatening airway obstruction due to pharyngeal oedema occurred immediately after extubation that required emergency tracheostomy. The airway obstruction did not improve well during the patient's postoperative course. Once pharyngeal oedema occurs in patients with metastatic tumor of upper cervical spine who undergo posterior cervical spine surgery following radiation therapy to the neck, the pharyngeal oedema may be constant for a long period of time.